The Implementation of Transportation Inclusion as a Social Welfare Policy Supporting Students Mobility - Nani, Sri; Laksmono, Bambang Shergi (International Journal Labs, 2023)
Background: East Jakarta City experienced the largest increase in the number of students in DKI Jakarta Province. The large number of students participating was followed by the many problems experienced by students such as the cost of transportation expenses for students. The DKI Jakarta Provincial Government issued a Jak Lingko transportation service policy as one of the steps to solving the problem. Aim: The focus of the research is to describe and analyze the implementation of the Jak Lingko transportation policy for the welfare of students in the City of East Jakarta as a form of supporting mobility. Method: This research approach is qualitative with descriptive research type. Interviews were conducted with 15 informants using a purposive sampling technique. Findings: The results of the study show that there are aspects of social welfare policy in the implementation of the Jak Lingko transportation policy that have fulfilled the basic Jak Lingko subsidy policy for students, the type of subsidy of the Jak Lingko subsidy policy, the process of distributing the Jak Lingko subsidy policy for students, and the funding system in accordance with Jak Lingko subsidy policy for students. There are obstacles in the implementation of the Jak Lingko transportation policy for students, namely the timeliness of the arrival of the Jak Lingko fleet has not been achieved.